The Brazilian archaeological program in Egypt: the first six years on TT123: assembling the puzzle - Pellini, José Roberto; Lemos, Caroline Murta (Revista do Museu de Arqueologia e Etnologia, 2023)
Created in 2015, the Brazilian Archaeological Program in Egypt (BAPE) develops transversal and participatory research on Egyptian soil. Since 2016, BAPE has been developing, together with the Egyptian government, an excavation project for Theban Tomb 123, located in Sheikh Abdel Qurna, Luxor, known as the Amenemhet Project. Tomb 123 served as a burial ground during the Pharaonic period and is currently a modern residence for Qurnawi families. This paper presents the first results of the research conducted at the site, offering a first interpretation based on the data collected so far, from an archaeological, historical and ethnographic perspective.